PANDANGAN KRIMINOLOGI TERHADAP TINDAK PIDANA PENCABULAN TERHADAP ANAK DI KOTA PADANG - Fauzi, Rahmat (Ensiklopedia Sosial Review, 2019)
Crime against children is rampant in the city of Padang, this is based on the data obtained shows that the number of sexual abuse cases in the city of Padang has increased, seen from the data obtained from the Padang City Police Resort in 2014 there were 2 (two) cases, in 2015 there are 5 (five) cases, in 2016 there are 6 (six) cases and in 2017 there are 7 (seven) cases. The increasing number of acts of sexual abuse that occur requires serious handling in an effort to overcome and provide legal protection. The settlement of criminal acts of sexual abuse can be resolved in mediation and some will proceed to cases of investigation and investigation. The approach used in this study is a sociological juridical approach. The conclusion of the study is: The form of criminal acts of sexual abuse against children that occurred in the city of Padang were in the form of: (a) intercourse with minors; (b) molesting minors; (c) escaping minors and intercourse with them; (d) rape; and (e) attempted rape. The motives and factors underlying the occurrence of criminal acts of sexual abuse against children in the city of Padang are: (a) factors of low education and economy; (b) environmental or residential factors; (c) alcohol factors; (d) factors lack of understanding of religion; and (e) the role of the victim